Development of Google Forms-Based Assessment as Learning with Autocrat Add-On to Assess Presentation Skills - Riyanto, Izory Roman; Hairida, Hairida; Enawati, Eny (Universitas Pendidikan Mandalika, 2025)
This study aims to develop an assessment as learning (AaL) instrument based on Google Forms with the Autocrat add-on to assess students' presentation skills, particularly in chemistry education. The instrument is designed to facilitate efficient self-assessment and peer assessment through the integration of Google Forms and Autocrat, enabling the automatic generation of assessment reports. The research employs the research and development (R&D) method using the ADDIE model, which includes the stages of analysis, design, and development. The instrument was validated by assessment, language, and media experts, and its effectiveness was tested through teacher and student responses. The validation results indicate that the instrument has a very high level of validity, with a content validity ratio (CVR) of 1.00 for all aspects of the presentation rubric. The linguistic aspect of the rubric scored 93%, while the media aspect achieved 95%, both categorized as excellent. Teacher and student responses to the instrument were also highly positive, with overall scores of 83% and 85%, respectively. The instrument is considered beneficial, engaging, and easy to use, making it an effective tool for enhancing presentation skills and supporting the implementation of assessment as learning in chemistry education.